2015
DOI: 10.1007/s00384-015-2246-2
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis to reappraise the role of adjuvant hepatic arterial infusion for colorectal cancer liver metastases

Abstract: Adjuvant hepatic arterial infusion improved the 5-year disease-free and overall survival rate, respectively. It should be recommended for patients with a high risk of recurrence, but these findings require prospective confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Use of HAIP for adjuvant therapy after liver resection has never gained widespread acceptance despite a randomized controlled and recent meta‐analysis reporting a strong benefit . Survival outcomes from several clinical trials and case series are shown in Table .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of HAIP for adjuvant therapy after liver resection has never gained widespread acceptance despite a randomized controlled and recent meta‐analysis reporting a strong benefit . Survival outcomes from several clinical trials and case series are shown in Table .…”
Section: Discussionmentioning
confidence: 99%
“…40 Use of HAIP for adjuvant therapy after liver resection has never gained widespread acceptance despite a randomized controlled and recent meta-analysis reporting a strong benefit. 17,41 Survival outcomes from several clinical trials and case series are shown in Table 5. The patients in these trials all received adjuvant HAIP FUDR infusion, and the early trials which used HAI 5-FU are not included.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al identified nine randomized and non-randomized studies with a pooled HR for OS of 0.75 (95% CI: 0.56-0.99) in favor of HAIC. 35 However, this study included several overlapping cohorts and 5 more recent studies were not included. Additional adequately powered RCTs are needed to investigate whether HAIC can improve survival.…”
Section: Discussionmentioning
confidence: 99%
“…employed for the treatment of hepatic tumors [98], but some literature has also been published on its use in pancreatic cancer [9,[30][31][32][33]. The exact tumor location and its supplying arteries determine through which vessels the chemotherapeutic infusion will be delivered.…”
Section: Immunomodulation After 125 I Seed Implantationmentioning
confidence: 99%